2001
DOI: 10.1614/0043-1745(2001)049[0460:aatogi]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Absorption and translocation of glyphosate in glyphosate-resistant cotton as influenced by application method and growth stage

Abstract: The influence of herbicide placement and plant growth stage on the absorption and translocation patterns of 14C-glyphosate in glyphosate-resistant cotton was investigated. Plants at four growth stages were treated with 14C-glyphosate on a 5-cm2 section of the stem, which simulated a postemergence-directed spray (PDS) application, or on the newest mature leaf, which simulated a postemergence (POST) application. Plants were harvested 3 and 7 d after treatment and divided into the treated leaf or treated stem, ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
75
0
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(82 citation statements)
references
References 19 publications
4
75
0
2
Order By: Relevance
“…Both cotton and sicklepod produce multiple reproductive sinks at various locations on the plant. Pline et al (2001) studied absorption and translocation patterns in 4-L and 8-L cotton using 14 Cglyphosate. When flowering was initiated, Pline et al (2001) found that cotton began translocating more glyphosate to the fruiting structures rather than to the roots.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both cotton and sicklepod produce multiple reproductive sinks at various locations on the plant. Pline et al (2001) studied absorption and translocation patterns in 4-L and 8-L cotton using 14 Cglyphosate. When flowering was initiated, Pline et al (2001) found that cotton began translocating more glyphosate to the fruiting structures rather than to the roots.…”
Section: Resultsmentioning
confidence: 99%
“…These negative effects on reproductive structures may be enhanced because of the translocation of glyphosate from source leaves to metabolic sinks such as reproductive organs, where it accumulates (Pline et al 2001;Viator et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Os resultados foram apresentados em gráficos, utilizando-se médias observadas e desvios-padrão. (Bariuan et al, 1999;Hetherington et al, 1999;Hall et al, 2000;Kirkwood et al, 2000;Reddy, 2000;Satchivi et al, 2000;Sharma & Singh, 2001;Pline et al, 2001). Em Sorghum halepenses e Elytrigia repens a absorção variou de 7 a 74% durante os períodos de 48 e 120 horas de exposição (Mcwhorter et al, 1980;Devine et al, 1983).…”
Section: Methodsunclassified
“…However, there are reports that following glyphosate treatment of glyphosate-resistant varieties of sugar beet, these plants accumulated toxic glyphosate metabolites [80]. More than that, the reproductive tissues of glyphosate-resistant cotton were shown to accumulate very high levels of the herbicide, 0.14 to 0.48 mg/g [81]; such concentration in food would be deadly (in the United States, the tolerable amount of residual glyphosate and its toxic metabolites in foodstuffs is 0.02 mg/kg dry wt). Regrettably, the data on the residual concentrations of herbicides in resistant plant varieties are not found in the published descriptions and other documentation.…”
Section: Food Risks Related To the Gmomentioning
confidence: 99%